Unveiling the digital future: perspectives of Hungarian physicians under 35 years old on eHealth solutions - Zsuzsa Győrffy; Zsuzsa Győrffy; Bence Döbrössy; Julianna Boros; Julianna Boros; Edmond Girasek (Frontiers in Digital Health)
BackgroundThe COVID-19 pandemic has catalysed the emergence of digital solutions in all areas of medicine. Our prior study on the digital health related experiences and opinions of Hungarian physicians highlights the crucial role of age in shaping attitudes towards digital health solutions among medical doctors. Our aim was to examine how under 35-year-old Hungarian physicians relate to digital technologies, the advantages and disadvantages they perceive, and how they would like to incorporate these technologies into their everyday medical practice.MethodsAs part of the “E-physicians and E-patients in Hungary” study, we conducted an online representative survey among medical practitioners in Hungary between July 2021 and May 2022 (n = 1,774). The main target group of our research were physicians under 35 years of age: n = 399 (25.3%). Besides descriptive statistical analyses, cluster analysis and binary logistic regression were applied to analyse the digital health related attitudes of the young age group.ResultsOur cluster analysis confirmed that younger doctors perceived more advantages (on average 7.07 items vs. 8.52 items) and disadvantages (on average 4.06 vs. 4.42) of digital health solutions. They also demonstrated greater familiarity with (8.27 vs. 9.79) and use of (1.94 vs. 2.66) a broader spectrum of technologies. Proficiency and active utilization of diverse technologies correlates with a more comprehensive understanding of both pros and cons, as well as a more realistic self-assessment of areas of further improvement. Doctors under 35 years express a notable demand for significantly increased incentives, both in terms of knowledge transfer/training and infrastructure incentives. Multivariate analyses revealed that young doctors, compared to their older counterparts, perceived enhanced patient adherence as one of the greatest benefits of digital health solutions. Additionally, young doctors expect that digital health solutions could reduce burnout.ConclusionOur results underscore the inevitable transformation of the 21st-century physician role: the success of digital health solutions hinges on active patient involvement and management, which requires proper patient education and professional support in navigating the digital space. Digital health solutions can be a bridge between different generations of doctors, where young people can help their older colleagues navigate the digital world.